Heterogeneous genetic (co)variances in simulated closed herds under selection - 10.4025/actascianimsci.v34i1.10934 - Daniela Andressa Lino-Lourenço; Carlos Antonio Lopes de Oliveira; Elias Nunes Martins; Meiby Carneiro de Paula Leite; Fabiana Martins Costa Maia; Alexandra Inês dos Santos (Acta Scientiarum. Animal Sciences, 2011)
Assuming that selection in closed herds can promote reduction in additive genetic variance, multiple regression models were used to estimate this change in additive genetic (co)variance component, over the years when the selection was done. Weights at 550 days (W550) were studied using simulated data of herds submitted to 20 years of selection. (Co)variance components were estimated assuming that the weight at 550 days was a new trait every five years, by multiple-trait analyses involving four traits in the animal model. Three multiple regression equations were fitted—RMI, RMM, RMF—estimating thus the additive genetic (co)variance components for the 20 years of selection and eight years prior to the selection process. The initial years of each generation of selection were used as a covariate in the RMI. In the RMM, intermediate years were used, and the final years were considered in the RMF. The equations showed high coefficients of determination. However, there was no difference in the adjustment between the models. It was observed that the multiple regression models can be used in the estimation of genetic (co)variance components, when heteroscedasticity is assumed over time due to the selection process.